Digital Literacy Transformation in Madrasah Ibtidaiyah for Arabic Language Learning Through Adab and Tahfidz Programs with Technological Touch - Ahmadi; Saad, Nurhasma Muhamad (UIN Sunan Kalijaga Yogyakarta, 2024)
The integration of digital literacy and technology into Arabic language education has emerged as a transformative approach to addressing both educational and cultural objectives in Madrasah Ibtidaiyah. This research investigates the synergistic relationship between modern technological tools and traditional Islamic teachings, focusing on Adab and Tahfidz programs as central components of the curriculum. By leveraging digital resources, educators aim to enhance language proficiency while simultaneously fostering moral character, ethical behavior, and spiritual awareness in students. The study employs a qualitative case study approach to gather in-depth insights into pedagogical strategies and technology integration at selected Madrasah Ibtidaiyah schools. Data were collected through interviews, classroom observations, and document analysis involving teachers and students as primary subjects. The research instruments included structured observation checklists, interview protocols, and reflective journals. Data analysis followed thematic coding to identify patterns and themes related to digital literacy practices and their impact on student engagement and learning outcomes. Findings reveal that integrating Adab and Tahfidz programs with technological tools enhances student motivation, facilitates immersive learning, and promotes ethical digital practices. This comprehensive approach supports the development of linguistic skills, cultural awareness, and spiritual values, offering a model for effectively blending tradition and innovation in Arabic language education.